Strategi Peningkatan Pengetahuan Kebencanaan pada Peserta Didik Tingkat SMA di Kota Medan - Eka Mawarni; Tantry Aulia Ardira (Geography Education Study Program, Universitas Samudra, 2020)
Natural conditions greatly affect human life. To overcome the risks and losses experienced by humans, we need knowledge, understanding, preparedness to prevent, know and anticipate more from high school students about various kinds of disasters or better known as disaster mitigation. Knowledge understanding and behavioral skills in preventing, detecting, anticipating disasters effectively and being transformed, disseminated through education. The purpose of this study is to introduce disaster management to high school students in the city of Medan. This research is a research that uses research and development with a population of students to determine the need for disaster learning through field surveys. The expected outcome of this research activity is that students are able to understand what a disaster is, how to avoid a disaster and what attitude must be taken when it occurs and after a disaster occurs.